Desempenho de dois materiais obturadores em biopulpectomias de molares decíduos: estudo clínico randomizado duplo-cego - Caldeira, Amanda Valentim (2020)
There are several types of root canal filling materials for primary teeth, such as zinc oxide and eugenol, iodoform paste and calcium hydroxide base paste and associations. It is necessary to determine which ones have the best physico-chemical and biological properties. This randomized, double-blind clinical study aimed to evaluate the performance of two filling materials after biopulpectomy in primary teeth. 43 biopulpectomies were performed on lower deciduous molars of children aged between 4 and 11 years. The teeth were selected and randomly distributed into two groups: Group I - Calen® (Calcium Hydroxide Paste and Polietileneglycol – PEG 400) thickened with zinc oxide and Group II - Feapex® (Calcium Hydroxide Paste and iodoform). Biopulpectomies were performed and teeth restored in a single session. Clinical success was considered as teeth with no pain, abscess / fistula, sensitivity to percussion and mobility. Radiographically considered successful, teeth with no periapical lesion / radiolucent interradicular area, integrity of the periodontal ligament, and adequate root canal filling. In addition, the conditions of the restorations were evaluated according to the modified USPHS criteria. Clinical and radiographic results were collected in the immediate postoperative period, at three, six and nine months after treatment. The percentage of clinical success was 100% and radiographic 78,9% for GI and 81,0% for GII. The distal roots, both in GI and GII, presented a high success rate in fillings. The restorations showed satisfactory clinical behavior (Alpha and Bravo score´s), in 72,5% of the cases, only 27,5% of the sample showed failures in the restorations, without secondary caries. It is concluded that biopulpectomies in primary teeth performed with both the Calen® paste thickened with zinc oxide and the Feapex® paste obtained a good clinical performance.